The Effect of Clinical Learning Environment on Nursing Student Satisfaction in East Java Province - Kuswantoro Rusca Putra; Alfrina Hany; Rustiana Tasya Ariningpraja (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2021)
Introduction: The clinical learning environment is a situation for the implementation of student practical learning. Satisfaction with the clinical learning environment is very important to foster a positive learning experience. This study aims to analyze the influence of the clinical learning environment on nursing student satisfaction. Methods: The study design used was an observational analysis with a cross-sectional approach to clinical nursing students in East Java Province with 451 student respondents. A consecutive sampling method was conducted. The Clinical Learning Environment Supervision Teacher (CLES T) instrument was used to assess learning environment variables and Clinical Learning Environment Inventory (CLEI), in particular, the satisfaction dimension was used to assess the satisfaction variable. Data analysis used the Spearman rank test and multiple linear regression. Results: There is a relationship between the clinical learning environment (pedagogic learning, leadership style, nursing care in the ward, the relationship of supervision, the role of nurse teacher) and the satisfaction of nursing clinic students (p = 0.000). Multiple linear regression analysis showed that the dimensions of pedagogic learning (t = 3.261; p = 0.001) and the role of the nurse teacher (t = 2.693; p = 0.007) had an effect on nursing student satisfaction. Conclusion: Student satisfaction is an important factor in the implementation of student clinical learning, so it is necessary to carry out good management by educational institutions and practice fields regarding the learning environment and improving the pedagogic atmosphere and the role of nurse teachers in clinical learning.